Promotion of tumor progression and cancer stemness by MUC15 in thyroid cancer via the GPCR/ERK and integrin-FAK signaling pathways. (November 2018) - Choi, Cheolwon; Tran, Nguyen; Ngu, Trinh; Park, Sae; Song, Min; Kim, Sung; Bae, Yun-Ui; Ayudthaya, Penchatr; Munir, Javaria; Kim, Eunbit; Baek, Moo-Jun; Song, Sujung; et al.
Abstract Thyroid cancer is the fifth most common cancer diagnosed in women worldwide. Notwithstanding advancements in the prognosis and treatment of thyroid cancer, 10–20% of thyroid cancer patients develops chemotherapeutic resistance and experience relapse. According to previous reports and TCGA database, MUC15 (MUCIN 15) upregulation is highly correlated with thyroid cancer progression. However, the role ofMUC15 in tumor progression and metastasis is unclear. This study aimed to investigate factors mediating cancer stemness in thyroid cancer.MUC15 plays an important role in sphere formation, as an evident from the expression of stemness markers includingSOX2, KLF4, ALDH1A3, andIL6 . Furthermore, ectopic expression ofMUC15 activated extracellular signal-regulated kinase (ERK ) signaling via G-protein–coupled receptor (GPCR)/cyclic AMP (cAMP) and integrin/focal adhesion kinase pathways. Interestingly, ectopic expression of MUC15 did not affectRAF /mitogen-activated protein kinase kinase (MEK )-mediatedERK activation. The present findings may provide novel insights into the development of diagnostic, prognostic, and therapeutic applications ofMUC15 in thyroid cancer.